Prospective clinical study of retinal microvascular alteration after ICL implantation - Tang, Chuhao; Zhang, Yu; Sun, Tong; Xie, Jianyang; Liu, Yiyun; Liu, Rongjun; Sun, Zhengze; Qi, Hong (Frontiers in Cell and Developmental Biology, 2023)
Purpose: To evaluate the retinal microvascular alteration after implantable collamer lens (ICL) implantation in moderate to high myopia patients using quantitative optical coherence tomography angiography (OCTA). Methods: This prospective cohort study included 50 eyes of 25 patients with preoperative spherical equivalent ≥ -3.00 D. Patients underwent bilateral ICL implantation at the Department of Ophthalmology, Peking University Third Hospital, from November 2018 to July 2019. OCTA was used to image the superficial and deep retinal capillary plexuses before ICL implantation surgery and at 3 months follow-up. Results: There was no significant difference in the microvascular density within each annular zone and all quadrantal zones of the superficial and deep layers found in myopia patients before and after ICL surgery. Conclusions: Levels of microvascular density in retinal capillary plexuses were stable, as detected by the OCTA, showing the high security of ICL implantation, which would not leave adverse effects on retina microvasculature in myopia patients.